La presencia de la vicuña como potencial agente dinamizador de turismo en la Reserva de Producción Faunística Chimborazo, año 2018 - Gallegos León, José Ignacio (2019)
This research work seeks to boost tourism in the Chimborazo Wildlife Production Reserve through the vicuña (Vicugna vicugna). For this, a diagnosis was made of the situation of the vicuña in the Chimborazo Faunal Production Reserve, using surveys aimed at the inhabitants of the buffer zone, the ASOCVICUÑA members who visited the reserve, in-depth interviews with knowledgeable professionals of the Vicuña as they are biologists, masto zóologos, paleontologists, ecologists and agronomists. Surveys of national and foreign tourists were carried out to identify the tourist segment interested in the vicuña. The research was developed based on tourists who visited the Chimborazo Fauna Production Reserve in 2018, the sample size was extracted by applying the corresponding statistical formula. The methodology to elaborate this interpretation manual was through the bibliographic review and web pages to then explore the habitat of this beautiful camelid. Thanks to this investigation, it was opportune to connect with the Ministry of the Environment that, through the training received with the subject of the shearing of the vicuña, the peasant leaders of the three provinces of Tungurahua, Bolívar and Chimborazo that make up the ASOCVICUÑA and those who are recommended to promote the Chaccu de la Vicuña, as a tourist activity of the reserve that would attract tourists seeking new experiences. In addition, the dissemination of the interpretive manual will allow the vicuña to be valued as a conservative species of the moor and water. The study of the Reserve's carrying capacity is of paramount importance for the survival of the species. Finally, this work is expected to be of help and encouragement for students who wish to continue researching the fascinating world of vicuñas